أثر أنظمة سعر صرف الدينار الجزائري على النمو الاقتصادي - عزي, خليفة; مسعودي, زكرياء; بن علي, آمال (جامعة الوادي - University of Eloued, 2019)
The choice and management of the exchange rate system is a critical aspect of economic management to protect competitiveness, macroeconomic stability and sustainable development. Discussions on any kind of exchange rate regimes continue to stimulate economic growth as one of the most important issues in the international economy, especially in light of the lack of declaration of the actual system adopted by some countries, The aim of this study is to clarify the effect of the Algerian dinar exchange rate on economic growth using the Autoregressive Distributed Lag (ARDL) model. The study concluded that there is no single system that balances the macroeconomic of a country at any time and anywhere, And that Algeria follows another undeclared for the Algerian dinar exchange rate regime , according to the Reinhart and Rogoff classification, which reveals that since the beginning of 1995, Algeria has followed the crawling band regime with the US dollar for its currency. The study also found a significant relationship between exchange rates regimes dinar de facto and economic growth.
The Impact of the Algerian Dinar Exchange Rate Regimes on the Economic Growth
مقال
Keywords: نظام النطاق الزاحف، النمو الاقتصادي، سعر الصرف، أنظمة سعر الصرف، نظام التعويم المدار; Crawling band regime, Economic growth, Exchange rate, Exchange rate regime, Managed float regime.